Preliminary Evaluations of [11C]Verubulin: Implications for Microtubule Imaging With PET - Lindberg, Anton; Mossine, Andrew V.; Aliaga, Arturo; Hopewell, Robert; Massarweh, Gassan; Rosa-Neto, Pedro; Shao, Xia; Bernard-Gauthier, Vadim; Scott, Peter J. H.; Vasdev, Neil (Frontiers in Neuroscience, 2021)
[11C]Verubulin (a.k.a.[11C]MCP-6827), [11C]HD-800 and [11C]colchicine have been developed for imaging microtubules (MTs) with positron emission tomography (PET). The objective of this work was to conduct an in vivo comparison of [11C]verubulin for MT imaging in mouse and rat brain, as well as an in vitro study with this radiotracer in rodent and human Alzheimer’s Disease tissue. Our preliminary PET imaging studies of [11C]verubulin in rodents revealed contradictory results between mouse and rat brain uptake under pretreatment conditions. In vitro autoradiography with [11C]verubulin showed an unexpected higher uptake in AD patient tissue compared with healthy controls. We also conducted the first comparative in vivo PET imaging study with [11C]verubulin, [11C]HD-800 and [11C]colchicine in a non-human primate. [11C]Verubulin and [11C]HD-800 require pharmacokinetic modeling and quantification studies to understand the role of how these radiotracers bind to MTs before translation to human use.